Relationship Between Adverse Tracheal Intubation Associated Events and PICU Outcomes*. Issue 4 (April 2017) - Parker, Margaret M.; Nuthall, Gabrielle; Brown, Calvin; Biagas, Katherine; Napolitano, Natalie; Polikoff, Lee A.; Simon, Dennis; Miksa, Michael; Gradidge, Eleanor; Lee, Jan Hau; Krishna, Ashwin S.; Tellez, David; et al.
Abstract : Objective: Tracheal intubation in PICUs is a common procedure often associated with adverse events. The aim of this study is to evaluate the association between immediate events such as tracheal intubation associated events or desaturation and ICU outcomes: length of stay, duration of mechanical ventilation, and mortality. Study Design: Prospective cohort study with 35 PICUs using a multicenter tracheal intubation quality improvement database (National Emergency Airway Registry for Children: NEAR4KIDS) from January 2013 to June 2015. Desaturation defined as Spo2 less than 80%. Setting: PICUs participating in NEAR4KIDS. Patients: All patients less than18 years of age undergoing primary tracheal intubations with ICU outcome data were analyzed. Measurements and Main Results: Five thousand five hundred four tracheal intubation encounters with median 108 (interquartile range, 58–229) tracheal intubations per site. At least one tracheal intubation associated event was reported in 892 (16%), with 364 (6.6%) severe tracheal intubation associated events. Infants had a higher frequency of tracheal intubation associated event or desaturation than older patients (48% infants vs 34% for 1–7 yr and 18% for 8–17 yr). In univariate analysis, the occurrence of tracheal intubation associated event or desaturation was associated with a longer mechanical ventilation (5 vs 3 d; p < 0.001) and longer PICU stay (14 vs 11 d; p < 0.001) but not with PICU mortality. The occurrence of severe tracheal intubation associated events was associated with longer mechanical ventilation (5 vs 4 d; p < 0.003), longer PICU stay (15 vs 12 d; p < 0.035), and PICU mortality (19.9% vs 9.6%; p < 0.0001). In multivariable analyses, the occurrence of tracheal intubation associated event or desaturation was significantly associated with longer mechanical ventilation (+12%; 95% CI, 4–21%; p = 0.004), and severe tracheal intubation associated events were independently associated with increased PICU mortality (OR = 1.80; 95% CI, 1.24–2.60; p = 0.002), after adjusted for patient confounders. Conclusions: Adverse tracheal intubation associated events and desaturations are common and associated with longer mechanical ventilation in critically ill children. Severe tracheal intubation associated events are associated with higher ICU mortality. Potential interventions to decrease tracheal intubation associated events and oxygen desaturation, such as tracheal intubation checklist, use of apneic oxygenation, and video laryngoscopy, may need to be considered to improve ICU outcomes. Abstract : Supplemental Digital Content is available in the text.